Star Wars. Episode VII, The force awakens [videorecording (Blu-Ray + DVD)] - Lucas, George, 1944- (LucasFilm, 2016)
As Kylo Ren and the sinister First Order rise from the ashes of the Empire, Luke Skywalker is missing when the galaxy needs him most. It's up to Rey, a desert scavenger, and Finn, a defecting stormtrooper, to join forces with Han Solo and Chewbacca in a desperate search for the one hope of restoring peace to the galaxy.